2014
DOI: 10.1002/9781118996652.ch14
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Glass Doping, Temperature and Time on the Morphology, Composition, and Iron Redox of Spinel Crystals

Abstract: Precipitation of large crystals/agglomerates of spinel and their accumulation in the pour spout riser of a Joule-heated ceramic melter during idling can plug the melter and prevent pouring of molten glass into canisters. Thus, there is a need to understand the effects of spinel-forming components, temperature, and time on the growth of crystals in connection with an accumulation rate. In our study, crystals of spinel [Fe, Ni, Mn, Zn, Sn][Fe, Cr] 2 O 4 were precipitated from simulated high-level waste borosilic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…The spinel crystals used to conduct Tests 2‐4 were extracted from High‐Ni‐Fe glass as described in Section 2 (Figure and Table ). The distance between probe electrodes as well as the depth of the spinel crystal layer were determined after the crucible had cool and could be cross sectioned and measured.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The spinel crystals used to conduct Tests 2‐4 were extracted from High‐Ni‐Fe glass as described in Section 2 (Figure and Table ). The distance between probe electrodes as well as the depth of the spinel crystal layer were determined after the crucible had cool and could be cross sectioned and measured.…”
Section: Resultsmentioning
confidence: 99%
“…Table shows the composition of the High‐Ni‐Fe glass in mass fraction of oxides. The spinel crystals for all testing were produced from the High‐Ni‐Fe glass by heat‐treatment in a double crucible for 7 days at 850°C. The crystals were recovered from the layer accumulated at the bottom of the crucible through overnight treatment with heated (60°C) 20% HNO 3 to dissolve the glass, and then treated with 5% HF to dissolve the residual silica gel.…”
Section: Methodsmentioning
confidence: 99%
“…An experimental glass composition used by the Pacific Northwest National Laboratory (PNNL) to study spinel settling, identified as Ni1.5/Fe17.5, was selected for this study because of its tendency to accumulate spinel crystals during relatively short heat treatment periods. 8,9 The composition of Ni1.5/Fe17.5 is given in Table 2-1. Fluorine and chlorine were removed from the targeted composition to simplify the procedure for fabrication at SRNL.…”
Section: Selection Of Experimental Glass Compositionmentioning
confidence: 99%
“…Two batches of the PNNL-SP glass composition were fabricated using reagent-grade materials (instead of dry AZ-101 simulant 8,9 ). These batches were identified as PNNL-SP2 and PNNL-SP4.…”
Section: Glass Fabricationmentioning
confidence: 99%
“…590 Backscattered electron SEM image of crystals of Spinel 15. Crystals were isolated from 591Ni1.5/Fe17.5 glass heat-treated at 900 °C for 4 days(Matyáš et al, 2014)…”
mentioning
confidence: 99%